IMPLIKASI GERAKAN PEMBAHARUAN MUHAMMAD ABDUH TERHADAP PARADIGMA STUDI ISLAM KONTEMPORER - Asep Saepulah (FASTABIQ: JURNAL STUDI ISLAM, 2021)
This article aims to analyze the renewal movement of Muhammad Abduh. Especially the implications for the paradigm of contemporary Islamic studies. Reform in Islam aims to bring Muslims to progress. The Islamic renewal movement emerged at the beginning of the 19th century due to the opinion that the door of ijtihad was closed and increasingly widespread among Muslims. Likewise tarekat with its negative influence. There is very little attention to science. So that Muslims experience a setback and fall into a static state. With the condition of the Muslims, some reform ideas emerged from several Islamic leaders who began to think about how to improve the quality and strength of Muslims again, including Muhammad Abduh. The importance of a comprehensive study of Muhammad Abduh's renewal movement is expected to be able to break the stagnation of thinking that exists among Muslims. The type of research in this article is a qualitative research literature study, using analytical-philosophical methods, by comprehensively analyzing studies related to Muhammad Abduh's renewal movement and its implications for the paradigm of contemporary Islamic studies. The results showed that Muhammad Abduh's renewal movement had an impact on the process of modernizing the education curriculum at Al-Azhar University, for example incorporating modern sciences that developed in Europe. Abduh's renewal movement was also carried out in the fields of fiqh, monotheism, state administration and so on. Thus opening the door of ijtihad and cleaning Islam from heresy and superstition. Then came Islam with a new method that was able to attract people's understanding rationally. Keywords: Renewal; Muhammad Abduh; Islamic Studies. Abstrak:Artikel ini bertujuan untuk menganalisis gerakan pembaharuan Muhammad Abduh. Terutama tentang implikasinya terhadap paradigma studi Islam kontemporer. Pembaharuan dalam Islam bertujuan untuk membawa umat Islam kepada kemajuan. Gerakan pembaharuan Islam muncul pada awal abad ke-19 akibat adanya pendapat bahwa pintu ijtihad tertutup makin meluas di kalangan umat Islam. Demikian juga tarekat dengan pengaruh negatifnya. Perhatian pada ilmu pengetahuan kurang sekali. Sehingga umat Islam mengalami kemunduran dan terjerumus pada keadaan statis. Dengan keadaan umat Islam tersebut, maka muncullah ide-ide pembaharuan dari beberapa tokoh pemuka Islam yang mulai memikirkan bagaimana meningkatkan mutu dan kekuatan umat Islam kembali, di antaranya Muhammad Abduh. Pentingnya studi tentang gerakan pembaharuan Muhammad Abduh secara komprehensif diharapkan mampu mendobrak kejumudan berpikir yang terdapat dikalangan umat Islam. Adapun jenis penelitian dalam artikel ini adalah penelitian kualitatif studi pustaka, dengan menggunakan metode analisis-filosofis, dengan menganalisis secara komprehensif kajian yang terkait dengan gerakan pembaharuan Muhammad Abduh dan implikasinya terhadap paradigma studi Islam kontemporer. Hasil penelitian menunjukkan gerakan pembaharuan Muhammad Abduh memiliki dampak kepada proses modernisasi kurikulum pendidikan di Universitas Al-Azhar, misalnya memasukkan ilmu-ilmu modern yang berkembang di Eropa. Gerakan pembaharuan Abduh pun dilakukan dalam bidang fiqh, tauhid, tata negara dan lain sebagainya. Sehingga membuka pintu ijtihad serta membersihkan Islam dari bid’ah dan khurafat. Kemudian muncullah Islam dengan metode baru yang mampu menarik pemahaman orang secara rasional. Kata Kunci: Pembaharuan; Muhammad Abduh;  Studi Islam.